Bacillus anthracis Phylogeography: New Clues From Kazakhstan, Central Asia - Shevtsov, Alexandr; Lukhnova, Larissa; Izbanova, Uinkul; Vernadet, Jean-Philippe; Kuibagarov, Marat; Amirgazin, Asylulan; Ramankulov, Yerlan; Vergnaud, Gilles (Frontiers in Microbiology, 2021)
This article describes Bacillus anthracis strains isolated in Kazakhstan since the 1950s until year 2016 from sixty-one independent events associated with anthrax in humans and animals. One hundred and fifty-four strains were first genotyped by Multiple Locus VNTR (variable number of tandem repeats) Analysis (MLVA) using 31 VNTR loci. Thirty-five MLVA31 genotypes were resolved, 28 belong to the A1/TEA group, five to A3/Sterne-Ames group, one to A4/Vollum and one to the B clade. This is the first report of the presence of the B-clade in Kazakhstan. The MLVA31 results and epidemiological data were combined to select a subset of seventy-nine representative strains for draft whole genome sequencing (WGS). Strains from Kazakhstan significantly enrich the known phylogeny of the Ames group polytomy, including the description of a new branch closest to the Texas, USA A.Br.Ames sublineage stricto sensu. Three among the seven currently defined branches in the TEA polytomy are present in Kazakhstan, “Tsiankovskii”, “Heroin”, and “STI”. In particular, strains from the STI lineage are largely predominant in Kazakhstan and introduce numerous deep branching STI sublineages, demonstrating a high geographic correspondence between “STI” and Kazakhstan, Central Asia. This observation is a strong indication that the TEA polytomy emerged after the last political unification of Asian steppes in the fourteenth century of the Common Era. The phylogenetic analysis of the Kazakhstan data and of currently available WGS data of worldwide origin strengthens our understanding of B. anthracis geographic expansions in the past seven centuries.